Measuring Parental Perceptions of Child Oral Health-related Quality of Life - Aleksandra Jokovic, MSc; David Locker, PhD; Marlene Stephens, MSc; David Kenny, PhD; (Blackwell Synergy, 2003)
The aim of this study was to develop and evaluate the P-CPQ, a measure of parental/caregiverperceptions of the oral health-related quality of life of children. This forms one component of the Child Oral Health Quality of Life Questionnaire (COHQOL